Analysis of District/City Economic Development Inequality in Jambi Province - Halim, Abd; Buhari, Ismail; Nurkodri, Moh Sahroni (Jurnal Prajaiswara, 2024)
This study aims to determine the level of economic development inequality in Jambi Province, and to determine the structure of the Regency / City economy based on Klassen Typology. This study employs the Williamson Index, a methodology that elucidates the interrelationship between regional disparity and the level of economic development. The analysis utilizes data on developed and developing economies, and it employs the Klassen Typology method to provide a comprehensive description of the pattern and structure of economic growth in each region. The results of this study are that the Inequality of Regency / City Economic Development in Jambi Province is in the high category. Williamson Index value 1.70 in 2012 Williamson Index value 0.50 in 2013. Williamson Index value of 0.55 in 2014 followed in 2016 with a Williamson Index value of 0.51. And the Williamson Index value is 0.60 in 2022. And in the medium category. Williamson Index value of 0.48 in 2015 The Williamson Index value was 0.46 in 2017. And followed in the next 3 years with a Williamson Index value of 0.47 and a Williamson Index value of 0.48 in 2021. The calculation of the Klassen Typology results in Jambi Province in the developed category area is Sungai Penuh City; The fast-growing category is occupied by the Kerinci, Merangin, Sarolangun, Batang Hari, Muaro Jambi, Tebo, Bungo and Jambi City regions; For the advanced but depressed category occupied by the East Tanjung Jabung and West Tanjung Jabung regions; then there are no relatively underdeveloped regions.